Studi Alternatif Perancangan Substructure Pada Jembatan Desa Kuala Tambangan - Eka Purnamasari; Revian Daffa Sosiawan (Media Ilmiah Teknik Sipil, 2021)
Abutmen is an under-bridge building located at both ends of the bridge pillars, serving as a load bearer that occurs on the upper structure of the bridge including the wind load load of the floor plate or force that occurs by the vertical load down. The province of South Kalimantan will widen the road, namely on the Batakan section of Kuala Tambangan Village, Tanah Laut Regency. Therefore, a bridge was built in Kuala Tambangan Village located in Batakan Section which is expected to support transportation. The length of the bridge span is 25.00 m and has a width of 6.00 m. The analysis was to plan an alternative structure of the lower building on the Kuala Tambangan Village bridge. Loading using LRFD (Load and Resistance Factor Design), loading standard for SNI 1725:2016 bridge and RSNI T-12-2004 (concrete structure planning for bridge). Based on the calculation of Substructure Abutment bridge has a length of 8.00 m, and a width of 2.80 m. The quality of concrete used is 25 MPa and the quality of reinforcing steel is BJ-TD 35 with a steel quality of 343 Mpa.